LEVERED BETA: INFLUENCE OF DEBT AND CORPORATE INCOME TAX ON COMPANY SYSTEMATIC RISK AND DISCUSSION ON THE CORRECT ALGEBRAIC EQUATION - Babanić, Mirko (The European Journal of Applied Economics, 2023)
Abstract:The increase in the share of debt in the capital structure is accompanied by an increase in the required return on equity because companies are exposed to higher financial risk. The beta coefficient of debt-financed companies differs from the beta coefficient of companies that are financed exclusively with equity. Namely, the beta coefficient, under the influence of financial leverage, tends to increase with the growth of indebtedness, that is the systematic risk measured by the coefficient beta of debt-financed companies is higher than the systematic risk of non-leveraged companies, due to financial risk. Because interest payments on the debt of leveraged companies are excluded as an expense from the tax base, corporate income tax reduces the beta coefficient of a company with debt, compared to the beta coefficient of the same company when income tax is abstracted. The higher the corporate income tax, that will be the lower the beta coefficient of companies that have debt in the capital structure. There are several algebraic equations, by different authors, for the beta coefficient of leveraged companies. The algebraic equation for the beta coefficient of leveraged companies, which is derived in this paper, was obtained using the net operating income approach.Keywords: systematic risk, beta coefficient, financial leverage, tax shield JEL: G11, G32, C10